2007
DOI: 10.1007/s11581-007-0065-3
|View full text |Cite
|
Sign up to set email alerts
|

Two-phase reaction mechanism during chemical lithium insertion into α-MoO3

Abstract: The phase transition during chemical lithium insertion into α-MoO 3 was investigated by chemical analysis, X-ray diffraction (XRD) and electrochemical characterisation. The samples have been prepared by reaction of various amounts of water-free lithium iodide with fine-particulate orthorhombic molybdenum trioxide in n-hexane (non-aqueous media), which yielded materials with different Li/Mo ratio. XRD investigations of these materials proved that the crystal structure of the layered α-MoO 3 has been changed aft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
32
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(34 citation statements)
references
References 11 publications
2
32
0
Order By: Relevance
“…Then, a new set of peaks is appearing corresponding to a new phase, which so far is not reported in the ICSD but should be close in term of nominal composition to Li x MoO 3-y (where x < 0.5 and y < 0.1). This phase was so far detected by Hashem et al [7] who pointed out this kind of reaction mechanism in Li x MoO 3 . Important to notice is that once this phase appears, there is almost no change in the XRD pattern indicating that we only extract lithium from this new structure (only shift visible then in the XRD patterns).…”
Section: Resultsmentioning
confidence: 55%
See 1 more Smart Citation
“…Then, a new set of peaks is appearing corresponding to a new phase, which so far is not reported in the ICSD but should be close in term of nominal composition to Li x MoO 3-y (where x < 0.5 and y < 0.1). This phase was so far detected by Hashem et al [7] who pointed out this kind of reaction mechanism in Li x MoO 3 . Important to notice is that once this phase appears, there is almost no change in the XRD pattern indicating that we only extract lithium from this new structure (only shift visible then in the XRD patterns).…”
Section: Resultsmentioning
confidence: 55%
“…Nevertheless, thanks to recent advances in synthesis methods that yield nanoscopic materials with enhanced functional properties, MoO 3 is currently intensively investigated as a potential cathode (positive electrode) material for high energy Liion batteries. It has been shown that downsizing of the MoO 3 particles leads to an impressive improvement of its electrochemical properties [6,7]. Recently we demonstrated that it was possible to boost the specific charge and simultaneously increase the stability of MoO 3 nanobelts by modifying their composition through mild ammonolysis [8].…”
Section: Introductionmentioning
confidence: 99%
“…This suggests that part of the Li þ ions, first introduced during the reduction reaction (discharge), later remain in the lattice. Such an effect has also been observed in V 2 O 5 [24] The mechanism of Li-ions intercalation into the a-MoO 3 has been described as the formation of three phases separated by bi-phase domains that are responsible for voltage plateaus in the first discharge curve [7,25,26]. It is believed that the Li 0.25 MoO 3 phase formed at 2.7 V vs. Li/Li þ is at the origin of the irreversible capacity at the end of the first charge.…”
Section: Structural Studiesmentioning
confidence: 87%
“…[19,20] The solar-intercalation battery is charged under low light intensities at open-circuitvoltage conditions with no external bias or current supplied.…”
Section: Introductionmentioning
confidence: 99%
“…Our findings provide direct experimental evidence of the two stage phase changes in the structure of MoO 3 during sodium-ion intercalation where previous techniques utilizing combinations of ex situ XRD or Transmission electron microscopy (TEM) and electrochemical characterization were indirect in nature. [19,20]…”
Section: Introductionmentioning
confidence: 99%